Cost Allocation and Cash Flow Issue in Shipbroking Companies: A Case Study of a Turkish Shipbroking Company - Danisman, Murat; Akkartal, Erkut (Archives of Business Research, 2022)
Purpose – The ship-broking companies are one of the key players of maritime transport and they need adequate financial control both on cost and income sides to provide sustainable service. The personnel costs need to be allocated properly within the scope of work. As it is their only income, commission collecting time is also needed to be predicted accurately together with related personnel cost. This article aims to introduce a methodology to construct the most accurate model predicting the duration of the operation and the income to guide the financial department of ship-broking companies and the same model can serve the other key players of maritime transport in the same way. Moreover, it may encourage other researchers to work on a similar purpose from the other perspectives in different sectors. Design / Methodology / Approach – In this research, 95 fixtures of a moderate Turkish ship-broking company are analysed. The data covers the fixtures concluded between January.2020 and December.2020. The model is constructed as per result of regression analyse and a simple validation is applied to check the reliability of the model. Findings – The research predicted that the duration of operation is dependent on the independent variables of sea voyage duration and ports stay whereas the duration of income is dependent on the independent variable port stays only. Validation results also support the reliability of the models. Result and Discussion – The research shows that for a shipbroking company duration of work and income can be predicted with a significant model. The model will provide a tool to the finance department to allocate the cost of employees involved during the operation in a more precise manner and also to organise the most accurate cash flow. But, it should be considered that the operation duration may exceed in some circumstances and the duration of collection of incomes can be varied as per company strategy. The model should be adjusted by each finance department within the working environment and strategy of the company.